Indoor comfort and energy performance of buildings in relation to occupants' satisfaction: Investigation in secondary schools of Cyprus - Katafygiotou, Martha; Serghides, Despina Kyprianou (My University, 2014)
Comfort standards state criteria to create adequate thermal comfort conditions in buildings. Requirements for comfort are critical especially to pupils' performance and welfare. This paper reviews and analyses the indoor comfort and specifically thermal comfort requirements based on international standards and previous studies. An investigation in secondary schools of Cyprus is carried out through a questionnaire campaign to examine the perception of indoor, environmental and energy parameters of schools in Cyprus. Nine schools are selected and a part of the questionnaire is developed within the framework of the Mediterranean (MED) Programme TEENERGY SCHOOLS (High energy efficiency schools in Mediterranean Area) which was dealing with the energy efficiency Mediterranean school buildings. For the analysis of the derived results, a statistical tool has been developed based on excel spreadsheets. Thermal comfort is always affected by the energy efficiency of buildings and vice versa. Therefore, further investigation of the energy efficiency of schools is examined through simulations according to the European Directive 2002/91/EC, using the official governmental software of Cyprus, iSBEMcy. The comparison assessment presents that there is a relation between the poor indoor quality conditions and the low-energy efficiency of buildings. This may occur due to the mismanagement of heating, ventilation and air conditioning systems in schools and the inefficient insulation of buildings.
Keywords: Energy efficiency; Environmental conditions; Indoor comfort; School buildings; Thermal comfort